ANALISIS PERUBAHAN TUTUPAN HUTAN DI TAMAN NASIONAL GUNUNG PALUNG, KALIMANTAN BARAT, MENGGUNAKAN PENGINDERAAN JAUH - Nurul Ihsan Fauzi; M Ari Wibawanto; Mahardika Putra Purba (Tengkawang : Jurnal Ilmu Kehutanan, 2020)
Monitoring forest cover to find out deforestation activities in a national park serves as an important task. This study aims to analyze forest cover changes in Gunung Palung National Park from 1989 to 2018. The method employs visual interpretation aided by supervised classification with the maximum likelihood method. Remote sensing data involved 18 Landsat images from 1989 to 2018 path/row 121/61. The results indicated that Gunung Palung National Park had 97,148 hectares of primary forest losing its 10% of its forest (since 1989). The primary forest decreased to 72,684 hectares in 1997 and 69,851 hectares in 2018. To date, primary forest cover has been found stable with secondary forests reaching to 25,050 hectares occupying 26% of Gunung Palung National Park area. Deforestation in Gunung Palung National Park was due to illegal logging and forest fires as a result of El Nio influence. The results of the analysis informed that there was an insignificant deforestation in Gunung Palung National Park during in the period of 2016 - 2018. In sum, conservation programs are encouraged to sustain, despite a decline in deforestation activities at Gunung Palung National Park. Keywords: Gunung Palung National Park, forest conservation, deforestationMonitoring tutupan hutan untuk mengetahui aktivitas deforestasi di taman nasional penting untuk dilakukan. Tujuan penelitian ini adalah untuk menganalisis perubahan tutupan hutan di TN Gunung Palung dari tahun 1989 2018. Metode yang digunakan adalah visual dibantu dengan klasifikasi terselia dengan metode maximum likelihood. Data penginderaan jauh yang digunakan adalah 18 citra Landsat tahun 1989 2018 path/row 121/61. Hasil penelitian menunjukkan sejak tahun 1989 TN Gunung Palung memiliki hutan primer seluas 97.148 hektar atau telah kehilangan 10% hutannya. Luas hutan primer menurun menjadi 72.684 hektar di tahun 1997 dan menjadi 69.851 hektar ditahun 2018. Saat ini kondisi tutupan hutan primer dalam kondisi stabil dengan hutan sekunder mencapai 25.050 hektar atau 26% dari luas TN Gunung Palung. Deforestasi di TN Gunung Palung disebabkan oleh pembalakan liar dan kebakaran hutan akibat pengaruh El Nio. Hasil analisis tidak ditemukan deforestasi di TN Gunung Palung selama rentang 2016 2018. Program konservasi harus tetap dilakukan walaupun telah terjadi penurunan aktivitas deforestasi di TN Gunung Palung.Kata kunci: Taman Nasional Gunung Palung, konservasi hutan, deforestasi